2013
DOI: 10.1021/jp4019298
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching of Hydrogen-Bonded Coumarin 102-Phenol Complex: Effect of Excited-State Hydrogen Bonding Strength

Abstract: The fate of intermolecular hydrogen bond (H-bond) upon electronic excitation of a H-bonded complex has been debated in literature. For a model H-bonded complex, coumarin 102 (C102)-phenol in a noninteracting solvent ethylene tetrachloride, time-resolved infrared spectroscopy experiment of Nibbering and coworkers suggests that the H-bond between the C102 and phenol ruptures upon electronic excitation (C. Chudoba et al. J. Phys. Chem. A1999, 103, 5625-5628). On the contrary, Zhao and Han have demonstrated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…This might be caused by the hydrogen bound formed between water molecules and coumarin 6, just as the quenching process between coumarin 102 and phenol molecules. 33 The emission peak of coumarin 6-loaded nanomicelles, which shifted to 492.3 nm (16 nm blue shift in Figure 4B), demonstrated that coumarin 6 was located in an apolar microenvironment. 34 No fluorescence quenching was displayed by the formulations, and polymers exhibited no fluorescence.…”
Section: Micelle Formationmentioning
confidence: 92%
“…This might be caused by the hydrogen bound formed between water molecules and coumarin 6, just as the quenching process between coumarin 102 and phenol molecules. 33 The emission peak of coumarin 6-loaded nanomicelles, which shifted to 492.3 nm (16 nm blue shift in Figure 4B), demonstrated that coumarin 6 was located in an apolar microenvironment. 34 No fluorescence quenching was displayed by the formulations, and polymers exhibited no fluorescence.…”
Section: Micelle Formationmentioning
confidence: 92%
“…From the potential energy scans (Figure ), one can easily follow the potential energy changes with the movement of proton towards the pyridinic nitrogen atom of NHM. Further a curve has been fitted based upon the Morse Equation and we have found the equilibrium ‐N−H distance, bond dissociation energy parameters. The equilibrium bond distance almost matches with the calculated distances from optimized geometries.…”
Section: Resultsmentioning
confidence: 99%
“…At each step, energy of this point calculated using DFT and TD-DFT method for S 0 and S 1 states respectively. Two very important parameters regarding hydrogen bonding, the equilibrium hydrogen bond distances (r 0 ) and the equilibrium hydrogen bond energy (D e ) can be calculated from the fitting of the curves with Morse equation [29] for each of the electronic states.…”
Section: Excited States and Spectral Simulation Upon Hydrogen Bondingmentioning
confidence: 99%